Finite element analysis of TC17 Ti alloy under high-speed cutting based on its friction model of deformation zone - Ping, Zhang; Youqiang, Wang; Wenhui, Liu (International journal of advanced manufacturing technology, 2018)
This study aims to remedy the deficiency in friction modeling of the deformation zone of TC17 Ti alloy under cutting process. First, the initial Johnson-Cook constitutive equation of TC17 Ti alloy as the subject of our study is established through SHPB dynamic impact test. Then, OXCUT backward induction solver is used to correct the initial Johnson-Cook constitutive equation for the alloy and yield the Johnson-Cook constitutive equation satisfying the “three-high feature” characteristics (high temperature, super-high strain, and high strain rate). Based on the four-factor, three-level orthogonal scheme designed according to the three-high-feature Johnson-Cook constitutive equation, 2D simulation is performed on the alloy. Accurate contact line models of the first and third deformation zones are established using the tool-chip contact parameters and the tool-workpiece contact parameters measured at the end of the simulation. Finally, 2D and 3D finite analysis of the alloy under high-speed cutting is conducted using the constitutive model and the contact length model for the deformation zone so established. As the rake angle of the tool increases, the pitch of the chip indention reduces, the shear zone of the first deformation zone narrows, and the average temperature during cutting is also notably lower. As the rake angle increases, the pitch of the spiral coil increases and then reduces; the coil radius is notably positively correlated to the rake angle of the tool. When the rake angle is 5°, the stress covers the entire cutting surface. In order to test the validity of finite element modelling, HSC test is carried out according to the finite element modelling plan; by comparison, the value of cutting force obtained from the finite element analysis is in reasonable agreement with the test value, with a maximum error smaller than 8%, which indicates that the Johnson-Cook constitutive equation, the friction models of the contact regions, and the finite element model are accurate and reliable.